USE BIFURCATION THEORY TO ASSESS THE STABILITY OF CURRENTS IN THE AXIAL COMPRESSOR - Кулик, М. С.; Терещенко, Ю. М.; Волянська, Л. Г. (Science-based technologies, 2009)
In the paper surge is considered as self-oscillation phenomenon. Possibility of surge prediction and effect on its development with the help of feedback controllers is investigated. Solving of a problem of non-linear control using the bifurcation theory is considered in the article. The Moore—Greitzer model (MG86) is used for research of processes in the compressor after loss gasdynamic stability. The model takes into account non-linear features of compressor characteristics and property of the compressor system. The model allows to determine what type of phenomena (rotating stall or surge) can appear, to establish distinctions in character surge oscillations and to estimate influence of various factors on area surge modes, to determine area of steady modes.